Marketing Research of the Production of Souvenir Packages - Іванна Іванівна Конюхова; Раїса Володимирівна Рибка (Технологія і техніка друкарства, 2016)
The article presents the results of analytical and market research of manufacturing process of souvenir cardboard packaging, identification of the needs and desires of consumers in packages decoration by the developed questionnaire and the conducted polls. The questionnaire consisted of 10 questions, each of which had four answers. Also important information for further statistical calculations was age, gender and employment of respondents. Total number of respondents — 135 people. In processing the results of various methods of mathematical and statistical processing of empirical data using the computer program STATISTICA. The methods of comparative analysis according to Student’s t-criterion, single-factor dispersion analysis (variation analysis and Sheffe test), correlation analysis (linear correlation according to Pearson), frequency tables at probability level p <0.05.